Socialization and Implementation of Midwifery Teleconsultation "Tanya Saja" app - Yanti, Irma; Suhartini, Leni; Suryani, Lilis; Hannie (Procedia of Social Sciences and Humanities, 2022)
The coronavirus (COVID-19) outbreak has spread globally and caused nearly 10,000,000 diagnosed cases and 500,000 deaths as of June 28, 2020. The impact of covid-19 can be greater on vulnerable populations. Pregnant women tend to be more physiologically and psychologically vulnerable to infectious diseases, putting them at higher risk of maternal complications. To avoid exposure to the COVID-19 virus, the government through the task force protocol recommends that health services in the form of education through teleconsultation, so that in exploring the challenges faced during the current covid-19 pandemic, smartphone technology in the form of applications with android operating information systems in support of information is provided. The purpose of making the Android-based "Ask Only" Midwifery Consultation application is as a promotive and preventive effort to spread the Covid-19 virus both to health workers and clients in providing remote midwifery care services. This devotional activity was held in December 2021. The method of devotion carried out by the form of socialization to the target of midwifery in Posyandu Kemuning VII Karawang Kulon Puskesmas Tanjungpura village with a total of 57 participants. The results of this activity obtained more participant data in the age group of ≤ 35 years, most participants from high school-PT education background, the majority of participants as Housewives, the majority of participants' knowledge about teleconsultation both, most participants gave an interested response using the Tanya Saja application.